Drift resonance and particle removal from helical plasma - Antufyev, O.; Pavlenko, I.; Girka, I. (Вопросы атомной науки и техники, 2015)
The effect of magnetic field perturbation on motion of deuterium, tritium and helium ions is studied theoretically and by numerical simulation of the charged particle motion in electromagnetic field. A method for alpha-particles (fusion reaction product) removal from plasma in helical device due to drift resonance formation is proposed. The point is that helium ion escapes from the confinement volume due to the natural drift in inhomogeneous magnetic field.